2023
DOI: 10.1021/acsinfecdis.3c00182
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Porphyromonas gingivalis Enriching Cancer Stem Cells by Inhibiting Programmed Cell Death Factor 4 in Esophageal Squamous Cell Carcinoma

Ruonan Li,
Yiwen Liu,
Fuyou Zhou
et al.

Abstract: Studies have confirmed that the colonization of Porphyromonas gingivalis (Pg) could promote the malignant evolution of esophageal squamous cell carcinoma (ESCC). Since pathogenic microorganisms can promote malignant tumor proliferation by inhibiting programmed cell death factor 4 (PDCD4) and the decrease of PDCD4 activity can enhance the stemness of cancer cells, we here investigated the functional mechanism by which Pg promoted ESCC chemoresistance and malignancy through inhibiting PDCD4 and enriching cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…After P. gingivalis elimination, PDCD4 expression was upregulated, and the percentage of CSCs, chemoresistance and malignancy were decreased in ESCC. 213 …”
Section: Overview Of Oral Microbiota In Carcinogenesismentioning
confidence: 99%
“…After P. gingivalis elimination, PDCD4 expression was upregulated, and the percentage of CSCs, chemoresistance and malignancy were decreased in ESCC. 213 …”
Section: Overview Of Oral Microbiota In Carcinogenesismentioning
confidence: 99%
“…Therefore, elucidating the key molecular targets of P. gingivalis during the initiation and progression of ESCC will provide valuable insights for early diagnosis. Targeted therapy studies have demonstrated that colonization by P. gingivalis suppresses the expression of programmed cell death factor 4, resulting in the accumulation of cancer stem cells within ESCC cells and facilitating malignant progression[ 85 ]. Moreover, prolonged colonization by P. gingivalis results in the upregulation of the inflammatory cytokine glycogen synthetase kinase 3β, which facilitates mitochondrial oxidative phosphorylation (mtOXPHOS) and fosters malignant progression in ESCC[ 86 ].…”
Section: Microbiology Approachesmentioning
confidence: 99%